(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
In the second half of the 20th century, the education system was cut off from the advanced achievements of world civilization and the historical roots of our people. A radical change in this situation, changes in the system of secondary specialized education in Uzbekistan, democratic transformations taking place in the republic and the requirements of a market economy, organization of the legal foundations of educational institutions, acceleration of educational reforms, consistency in this direction and the new law, which serves to ensure continuity, meet the need for personnel, analyzed the issues of reforming the education system